An Examination on Edip Yuksel's Interpretation of Q. 4:34 - Sitanggang, Nadya Utari Boru (UIN Sunan Kalijaga Yogyakarta, 2017)
Q.4:34 is frequently used to justify menâ€™s domination over women. There are some keywords in this verse that Edip Yuksel thought have been mistranslated and misunderstood by many scholars, then he reinterpreted them. The authors employed five principles to establish their work, â€œQuran: A Reformist Translationâ€. Those five principles are what shaped the work and what influenced the final result of the interpretation. This article uses their principles as tool to criticize the interpretation, so it is called internal criticism. Finally, this work concludes that Edip Yukselâ€™s interpretation valuated by the five principles is relatively implemented well, the lack is located in the authorâ€™s attitude to decide the meaning rashly without explaining the reason they finally chose the meaning after criticizing otherâ€™s work.Keywords: 4:34, mistranslated, misunderstood, internal criticism.